The Kidney Transplant Mission: Breaking Ground, Saving Lives - Obiatuegwu Kenenna; Aniede Ernest (American Journal of Internal Medicine, 2026)
Introduction: The success of kidney transplantation depends on key factors including appropriate patient selection, satisfactory donor compatibility test, early commencement of immunosuppressant and premedication, good surgical technique with experienced transplant team, intensive post-surgery care, serial daily monitoring of renal function, early renal Doppler study as well as continuous immunosuppression and prompt follow up. We report our initial experience at BeWell Kidney Transplant Mission with emphasis on common contemporary indices that influence outcome of kidney transplantation including etiology, patient selection as well as serial outcome amongst donors and recipients following a successful kidney transplant camp. Methodology: This is a prospective observational study involving patients who had kidney transplantation secondary to varying degree of chronic kidney disease over an 8-month period. Structured questionnaire was designed to obtain relevant information. Data analysis was via python 3.x and results represented in tables and charts. Results: A total of 30 kidney transplantation were carried out within the study period. 80% of the recipients were males. All the donors were males. The youngest recipient was 22 years and the oldest was 80 years with a mean age of 61.53 +/- 3.04. Hypertension coexisting diabetes mellitus was the leading cause of kidney failure. Left donor nephrectomy dominated in 83.3% of cases while right donor nephrectomy was performed in only 17.7%. Donor stay ranges from 5 to 6 days while recipients were discharged between 8 to 10 days. The 6 months and one year prognosis was excellent. 96.7% of recipient had improved QoL with return to normal life. Conclusion: Our impressive outcome was probably due to strictly adherence to our local protocol which includes good patient selection, complete HLA typing, cross matching and DSA quantitative analysis, legal documentation, early commencement of immunosuppression, experience transplant team, good surgical techniques, high dependency unit monitoring until discharge. Improving understanding of how to best address these indices can empower transplant centers with appreciable progress toward a worthwhile experience.